Recycled aggregate in 3D printing concrete technology and the future of it - Parvin Montazeri (مهندسی و مدیریت ساخت)
Recent studies indicate that recycled concrete aggregates (RCA) can achieve mechanical properties comparable to those of conventional aggregates, thereby facilitating their use in structural applications without compromising safety or durability. For instance, research has demonstrated that the incorporation of larger aggregates in large particle 3D concrete printing methods can significantly reduce the volume of cement required, thus contributing to lower environmental impact while maintaining structural integrity. Additionally, the utilization of supplementary cementitious materials has been shown to improve the bonding characteristics and overall performance of recycled aggregate concrete.The review further elucidates the role of innovative recycling techniques and smart materials in augmenting the effectiveness of recycled aggregates within 3D printing processes. These advancements not only enhance the quality of the recycled materials but also promote their acceptance within the industry. Moreover, the discussion extends to the implications of regulatory frameworks and public perception, which play critical roles in influencing the widespread adoption of sustainable construction practices.In conclusion, this literature review presents a comprehensive analysis of the current state of research on recycled aggregates in 3DCP technology, highlighting both the challenges and the significant potential for their integration in promoting sustainability within the construction sector. It concludes with insights into future trends and the necessity for ongoing research to optimize the use of recycled aggregates, positioning them as a key component in the evolution of environmentally responsible building practices. As the industry moves forward, the continued exploration of the interplay between recycled materials and advanced construction technologies will be vital in shaping a more sustainable future for concrete production and construction methodologies.